Scope of sexual and reproductive health care receipt among young males aged 15-24 - Marcell, Arik V. (J Adolesc Health, 2017)
OBJECTIVE: To describe young men’s sexual and reproductive healthcare (SRHC) receipt by sexual behavior and factors associated with greater SRHC receipt. METHODS: 427 male patients aged 15–24 were recruited from 3 primary care and 2 STD clinics in one urban city. Immediately after visit, survey assessed receipt of 18 recommended SRHC services across four domains: screening history (sex health, STD/HIV test, family planning); laboratories (STDs/HIV); condom products (condoms/lubrication); and counseling (STD/HIV risk reduction, family planning, condoms); and demographic, sexual behavior and visit characteristics. Multivariable Poisson regressions examined factors associated with each SRHC subdomain adjusting for participant clustering within clinics. RESULTS: 90% were non-Hispanic Black, 61% aged 20–24, 90% sexually active, 71% had female partners (FP), and 20% male or male and female partners (M/MFP). Among sexually active males, one in ten received all services. Half or more were asked about sexual health and STD/HIV tests, tested for STDs/HIV, and counseled on STD/HIV risk reduction and correct condom use. Fewer were asked about family planning (23%), provided condom products (32%), and counseled about family planning (35%). Overall and for each subdomain, never sexually active males reported fewer services than sexually active males. Factors consistently associated with greater SRHC receipt across subdomains included: having M/MFP vs. FP, routine vs. non-STD-acute visit, time alone with provider without parent, and seen at STD vs. primary care clinic. Males having FP vs. M/MFP reported greater family planning counseling. CONCLUSIONS: Findings have implications for improving young men’s SRHC delivery beyond narrow scope of STD/HIV care.